Mathematical study of the thermoluminescence process in K2YF5:Tb3+ - Kadari, Ahmed (2014)
This paper presents results of studying the simulated thermoluminescence (TL) glow curve in potassium–yttrium double fluoride doped with trivalent optically active Tb3+ ions (K2YF5:Tb3+). Samples have been irradiated with different doses (0.24, 2.4 and 24 Gy) of beta particles. Four trapping states and one kind of recombination-centre model have been used in this simulation. The activation energy and order of kinetics are determined using the general-order kinetic model. The results obtained using the authors’ proposed models were tested and compared with the experimental glow curve of K2YF5:Tb3+. The comparison has shown that the proposed model can predict more accurately and easily the behaviour of the TL glow curve at three different doses.